Exploring the role of curcumin in mitigating oxidative stress to alleviate lipid metabolism disorders - Cheng, Maojun; Ding, Fang; Li, Liyang; Dai, Changmao; Sun, Xiaolan; Xu, Jia; Chen, Feier; Li, Mingxiu; Li, Xueping (Frontiers in Pharmacology, 2025)
Lipid metabolism plays a crucial role in maintaining homeostasis and overall health, as lipids are essential molecules involved in bioenergetic processes. An increasing body of research indicates that disorders of lipid metabolism can contribute to the development and progression of various diseases, including hyperlipidemia, obesity, non-alcoholic fatty liver disease (NAFLD), diabetes mellitus, atherosclerosis, and cancer, potentially leading to poor prognoses. The activation of the oxidative stress pathway disrupts lipid metabolism and induces cellular stress, significantly contributing to metabolic disorders. A well-documented crosstalk and interconnection between these metabolic disorders exists. Consequently, researchers have sought to identify antioxidant-rich substances in readily accessible everyday foods for potential use as complementary therapies. Curcumin, known for its anti-inflammatory and antioxidant properties, has been shown to enhance cellular antioxidant activity, mitigate oxidative stress, and alleviate lipid metabolism disorders by reducing reactive oxygen species (ROS) accumulation. These effects include decreasing fat deposition, increasing fatty acid uptake, and improving insulin sensitivity. A review of the existing literature reveals numerous studies emphasizing the role of curcumin in the prevention and management of metabolic diseases. Curcumin influences metabolic disorders through multiple mechanisms of action, with the oxidative stress pathway playing a central role in various lipid metabolism disorders. Thus, we aimed to elucidate the role of curcumin in various metabolic disorders through a unified mechanism of action, offering new insights into the prevention and treatment of metabolic diseases. Firstly, this article provides a brief overview of the basic pathophysiological processes of oxidative stress and lipid metabolism, as well as the role of oxidative stress in the pathogenesis of lipid metabolism disorders. Notably, the article reviews the role of curcumin in mitigating oxidative stress and in preventing and treating diseases associated with lipid metabolism disorders, including hyperlipidemia, non-alcoholic fatty liver disease (NAFLD), atherosclerosis, obesity, and diabetes, thereby highlighting the therapeutic potential of curcumin in lipid metabolism-related diseases.